Phenotypic plasticity in host plant preference of the willow leaf beetle Phratora vulgatissima: the impact of experience made by adults. (27th May 2014) - Austel, Nadine; Björkman, Christer; Hilker, Monika; Meiners, Torsten
Abstract Knowledge of the plasticity of Phratora vulgatissima (Colepotera: Chrysomelidae) behavioural responses to cues of its willow host plants is essential for understanding host affiliations of this species and for developing management strategies. We investigated how the experience obtained by adult P. vulgatissima with two different willow species shapes olfactory, feeding and oviposition preferences in the laboratory. The willow species differed in their leaf odours and phenolic glycoside contents. Females that had experienced Salix viminalis (Salicaceae) neither discriminated between odours of S. viminalis and Salix dasyclados, nor between blends of green leaf volatiles (GLV) that mimic quantitatively those released by S. viminalis and S. dasyclados. However, when females had experienced S. dasyclados, they preferred the experienced odour of S. dasyclados and the respective GLV blend to the odour of S. viminalis or its GLV blend. By contrast, regardless of their experience obtained in the adult stage, females preferred S. viminalis over S. dasyclados for feeding and oviposition. Exposure of beetles to odour of stands with various willow species might affect the experience‐induced olfactory preference for a single species and thus impair host location success.